2017
DOI: 10.1007/s12639-017-0892-8
|View full text |Cite
|
Sign up to set email alerts
|

Microfilaruria by Dirofilaria immitis in a dog: a rare clinical pathological finding

Abstract: A 6-year-old Labrador with history of hyperpnea, respiratory distress, ascites and paraparesis, presented microfilariae in the blood smear, cytology of the abdominal fluid and urine. The positive samples were confirmed by multiplex-PCR (COI gene) and sequencing, and presented 98% homology to (GenBank accession nos. KC107805.1, EU159111.1, EU163945.1, DQ358815.1, and AJ537512-1). Based on the presented results and the physiopathology of the heartworm disease, molecular techniques may be helpful and accurate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
4
0
4
Order By: Relevance
“…Outros achados macroscópicos observados foram: ascite e congestão visceral, particularmente do fígado, baço e dos rins (Figuras 3A, 4A e 5A). Sabe-se que alterações como ascite e congestão visceral são evidências de insuficiência cardíaca resultante do comprometimento cardíaco provocado pela dirofilariose (MONOBE et al, 2017).…”
Section: Resultsunclassified
“…Outros achados macroscópicos observados foram: ascite e congestão visceral, particularmente do fígado, baço e dos rins (Figuras 3A, 4A e 5A). Sabe-se que alterações como ascite e congestão visceral são evidências de insuficiência cardíaca resultante do comprometimento cardíaco provocado pela dirofilariose (MONOBE et al, 2017).…”
Section: Resultsunclassified
“…A presença de hematúria e insuficiência renal aguda é frequentemente associadas, no entanto a presença de larvas na urina (microfilaruria) é extremamente rara, incomum e foram encontradas no animal em questão, fato esse que revela a evolução do microfilária no sistema excretor no animal, que dificulta ainda mais o tratamento e perspectiva de regressão do quadro do animal (Kaewthamasorn et al, 2008;Monobe et al, 2017).…”
Section: Resultsunclassified
“…Previous studies have demonstrated glomerular changes secondary to heartworm disease, including thickening and vacuolation of the glomerular basement membrane, deposition of immune complexes in the glomerular basement membrane leading to immune complex-mediated glomerulonephritis, proliferation of mesangial cells and matrix and occasionally the presence of micro lariae lodged in the glomeruli [10,11,12]. Rarely, micro lariae have be detected on urine sedimentation examinations, and can be associated with hematuria, proteinuria, or other signs of renal disease [27].…”
Section: Discussionmentioning
confidence: 99%